Nomenclatural notes on triporous taxa of Chrysococcus G.A. Klebs (Chrysophyceae) - Kapustin, Dmitry A. (Phytotaxa, 2019)
The genus Chrysococcus G.A. Klebs (1892: 413) comprises unicellular planktonic chrysophytes with cells surrounded by a lorica. Lorica shape and size, ornamentation, number of pores and presence or absence of stigma are the main features for distinguishing taxa (Starmach 1985; Nicholls & Wujek 2015). In his treatment Starmach (1985) listed 25 species of Chrysococcus and several intraspecies taxa.